2016
DOI: 10.1002/acr.22711
|View full text |Cite
|
Sign up to set email alerts
|

Association of Light‐Intensity Physical Activity With Lower Cardiovascular Disease Risk Burden in Rheumatoid Arthritis

Abstract: Objective: To characterize physical activity (PA) in individuals with rheumatoid arthritis (RA) and determine the associations between PA participation in light to moderate intensities and cardiovascular risk factors, disability, and disease activity. Methods: Cross-sectional study using data from two RA cohorts. PA was measured using an accelerometry-based activity monitor, and characterized as minutes/day in sedentary (≤1 metabolic equivalent-MET), very light (1.1–1.9 METs), light (2–2.9 METs), and moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 45 publications
6
49
1
9
Order By: Relevance
“…In a cross-sectional study, Khoja et al, (2016) reported SB measured by the SWA, to be inversely related to disease activity score in a group of RA patients [63]. However, as with all crosssectional studies, the causal direction of this association cannot be determined.…”
Section: Disease Activitymentioning
confidence: 96%
See 4 more Smart Citations
“…In a cross-sectional study, Khoja et al, (2016) reported SB measured by the SWA, to be inversely related to disease activity score in a group of RA patients [63]. However, as with all crosssectional studies, the causal direction of this association cannot be determined.…”
Section: Disease Activitymentioning
confidence: 96%
“…This underestimation was suggested to be due to the elevated resting energy expenditure observed in this patient population, relative to healthy adults in which the proprietary-SWA-algorithms tested were developed [61]. As such, these findings support the thesis that inaccuracies in sedentary time estimation may arise when studies in RA employ SB algorithms derived from calibration studies in healthy adults (e.g.,<100cpm - Table 3) [59,60,62,63]. [59,72].…”
Section: Application and Validity Of Sedentary Behaviour Measurement mentioning
confidence: 99%
See 3 more Smart Citations